Diffusion bonding effects on the adhesion of tungsten dust on tungsten surfaces - P. Tolias (Nuclear Materials and Energy, 2020)
High temperature excursions have the potential to strongly enhance the room temperature adhesion of tokamak dust. Planar tungsten substrates containing adhered nearly monodisperse spherical tungsten dust have been exposed to linear plasmas and vacuum furnaces. Prolonged thermal treatments of varying peak temperature and constant duration were followed by room temperature adhesion measurements with the electrostatic detachment method. Adhesive forces have been observed to strongly depend on the thermal pre-history, greatly increasing above a threshold temperature. Adhesive forces have been measured up to an order of magnitude larger than those of untreated samples. This enhancement has been attributed to atomic diffusion that slowly eliminates the omnipresent nanometer-scale surface roughness, ultimately switching the dominant interaction from long-range weak van der Waals forces to short-range strong metallic bonding.